ACHIEVEMENT MOTIVATION OF STUDENTS IN AGRICUITURE COLLEGE / UNIVERSITY. - Naji, Ashwaq A.; alsibak, Maha fadel; Lafta, Ahmed H. (Diyala Agricultural Sciences Journal, 2010)
Achievement motivation considered one of incentives that motivated student towards Achievement in employed . area in Agricultural college . for that the research aimed to determine the Achievement Motivation level of student the fourth stage in Agricultural college . the sample of the research consisted of 140 students from fourth stage for all departments in the college for the year 2007 – 2008 . Data was collected questioner , consist of to dominos first dominate was for measurement of Achievement Motivation for students it was consist of 38 items and it was degrees for five levels , agree with high , agree with , disagree with high , disagree with very high . The Achievement Motivation degree was between 38 – 175 degree from 38 – 190 degree . The mean was 134 degree . The conclusion was showed low mean of Achievement Motivation of students , and the related was non significant between the Achievement Motivation level and each of the variables , marred case , six , back round education of parents . The research recommend elevated the Achievement Motivation students throw produced the material and encouraging for students throw and after ending of Agricultural college .